Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T09:05:34+01:00
A) 1/3 x - 2 = x+2
1/3x-x=2+2
-2/3x=4 |:-2/3
x=6
b) 1 - 6/7x = 4/7
-6/7x=4/7-1
-6/7x=-3/7 |:-6/7
x=1/2
x=0,5
c) 6 (1/4 x - 2) = 18
1,5x-12=18
1,5x=30 |:1,5
x=20
2009-11-22T09:33:45+01:00
A)
1/3x-2=x+2 /*3
x-6=3x+6
x-3x=6+6
-2x=12/-2
x=-6

b)
1-6/7x=4/7 /*7
7-6x=4
-6x=4-7
-6x=-3/:-6
x=1/2

c)
6(1/4x-2)=18
6/4x-12=18 /*4
6x-48=72
6x=72+48
6x=120/:6
x=20
2009-11-22T09:44:00+01:00
A) ⅓ x - 2 = x+2
⅓x-x=2+2
- ⅔x=4 /:(-⅔)
x=-6

b) 1 - ⁶/₇x = ⁴/₇
- ⁶/₇x = ⁴/₇ +1
⁶/₇x = ¹¹/₇ /:⁶/₇
x=¹¹/₆
x=1 ⁵/₆
c) 6 (¼ x - 2 ) = 18
1 ½x - 12=18
1 ½x =18+12
1 ½x =30 /:1½
x=20